PERAN DAN PARTISIPASI MASYARAKAT DALAM PELESTARIAN DAN PENGEMBANGAN BUDAYA - Sambung Widodo (BRIN, 2004)
The increasing role and participation of the community needs to be fostered through continuous effort without stopping in the long term. The efforts needed includes several stages, namely (Javanese): tepung (recognizing), dunung (knowing), srawung (understanding). At an early stage, the community needs to recognize (tepung) what is the potential for its natural and cultural resources. The next stage, the community needs to know (dunung) how to develop and utilize its potential. In the end, the community understands (srawung) and appreciates that the potential of natural and cultural resources that can be maintained and developed can provide benefits to their lives, increase material and spiritual well-being.